Detection of Hepatitis B Core Antigen by Phage Display Mediated Immuno-Taqman Real-Time Polymerase Chain Reaction - Monjezi, Razieh (2011)
Hepatitis B virus (HBV) causes acute and chronic viral hepatitis and it is closely related to the development of liver cirrhosis and hepatocellular carcinoma. One of the HBV serological markers is hepatitis B core antigen (HBcAg) and it is closely related to the viral DNA load. Phage display mediated immuno-PCR (PD-IPCR) is a new strategy that combines the advantages of phage display technology and immuno-PCR (IPCR). IPCR combines the versatility of enzyme-linked immunosorbent assay (ELISA) with the amplification and sensitivity of PCR. As a consequence, IPCR leads to about 1,000- to 10,000-fold improvement in sensitivity as compared to a conventional ELISA.Previously, by the aid of phage display technology, a fusion bacteriophage bearing the sequence WSFFSNI, which interacts tightly with HBcAg was isolated. This fusion phage has the potential to be further developed as a diagnostic reagent for IPCR. Traditionally, the fusion phage required in this study has been purified by cesium chloride (CsCl) density gradient ultracentrifugation. This conventional method of phage purification is highly labourious and time consuming. In order to overcome the disadvantages of the conventional purification method, a simple, rapid and efficient method for purification of M13 phage based on anion exchange chromatography was established. A pre-packed SepFast™ Super Q column connected to a fast protein liquid chromatography system was employed to capture released phages in clarified Escherichia coli fermented broth. An average yield of 74% was obtained from a packed bed mode elution using citrate buffer (pH 4), containing 1.5 M NaCl at 1 ml/min flow rate. The purification process was shortened substantially to less than 2 h from 18 h in the conventional ultracentrifugation method. SDS-PAGE revealed that the purity of particles was comparable to that of CsCl gradient density ultracentrifugation method. The purified fusion phage was used for developing a phage display mediated TaqMan real-time immuno-PCR for detecting HBcAg. The initial conditions for real-time PCR like probe concentration and annealing temperature were optimised. The best threshold cycle (Ct) was obtained when 100 nM of probe with an annealing temperature of 60 ºC were used. The efficiency of the real-time PCR reaction based on the slope of a standard curve was 96.7%. This method detected as low as 5 ng of HBcAg by using 108 pfu/ml of the fusion phage. The specificity of the assay was assessed by testing the reactivity of the fusion phage with healthy human sera. Moreover, the developed assay was also used to detect HBcAg in the sera of HBV positive patients. Based on the cutoff value which was obtained from healthy serum reactivity with the phage, the assay managed to detect the HBcAg in the sera of HBV positive patients. In conclusion, the phage displayed peptide which interacts tightly with HBcAg and its encoding DNA can replace monoclonal antibody and chemically bond DNA, respectively.